السرعة المعرفية وعلاقتها بالانتباه التنفيذي والإدراك البنائي لدى طلبة المرحلة المتوسطة في المدارس الأهلية - السباب، أزهار محمد مجيد نصيف (جامعة عين شمس - كلية الآداب, 2020)
يوصف عالمنا اليوم تكنلوجي سريع التغير وتتضاعف فيه المعرفة البشرية خلال بضع السنين، مما يفرض على الطالب أن يثبت جدواه وسط هذه الأمواج من التكنلوجيا المتغيرة وتتضاعف معرفة والصمود امامها بل الانتباه لها للتغلب عليها وأدراك المواقف لمواجهة المشكلات التي تتطلب بذل المزيد من العمليات العقلية الداخلية وحلها بسرعة المعرفية مع التهيؤ لمزيد من اتخاذ القرارات، البحث الحالي يستهدف إلى معرفة: 1- السرعة المعرفية والانتباه التنفيذي والادراك البنائي لدى طلبة المرحلة المتوسطة في المدارس الأهلية. 2- التعرف على الفروق ذات الدلالة الإحصائية في السرعة المعرفية والانتباه التنفيذي والإدراك البنائي تبعا لمتغير الجنس (ذكور-اناث). 3- ثم معرفة مدى اسهام الانتباه التنفيذي والادراك البنائي الكلي للسرعة المعرفية لدى طلبة المرحلة المتوسطة في المدارس الأهلية، تكونت عينة البحث من (400) طالبا وطالبة تم اختيارهم بطريقة عشوائية، وتم بناء اختبار للسرعة المعرفية من (28) فقرة ويجب على المفحوص اختيار بديل واحد الصحيح من بين خمسة بدائل، وكذلك تم بناء اختبار الانتباه التنفيذي من (20) فقرة ويجب على المفحوص اختبار بديل واحد الصحيح من بين أربعة بدائل، واعتمدت الباحثة على اختبار عبد الله (2014) للإدراك البنائي المكون من أربعة فقرات يعطي تفسيرات، أظهرت النتائج أن الطلبة لديهم سرعة معرفية وانتباه تنفيذي لصالح الاناث وادراك بنائي لصالح الذكور، كما أظهرت النتائج إلى أن الانتباه التنفيذي والادراك البنائي يسهمان في زيادة السرعة المعرفية ولا يوجد فروق بين الذكور والاناث بذلك.
Our world today is characterized by a fast-changing technology and a doubling of human knowledge over the course of a few years, which forces the student to prove his worth amidst these waves of changing technology and double the knowledge and steadfastness in front of them, but attention to them to overcome them and awareness of situations to face problems that require more internal mental processes and resolve quickly Cognitive with preparation for further decision-making. The current research aims at knowing: - 1 - The speed of knowledge, operational attention and constructive awareness among middle school students in private schools 2 - Identification of differences of statistical significance in the speed of knowledge and operational attention and cognitive perception depending on the gender variable (male_ anath) 3 - To know the extent of the contribution of the executive attention and the overall structural awareness of the cognitive speed of middle school students in the civil school. The sample consisted of (400) students randomly selected. A cognitive speed test was constructed from (28) The correct one of the five alternatives, as well as the test of the executive attention of (20) paragraph, the tested one must be tested one of the four correct alternatives, and the researcher adopted the Abdullah test (2014) for the four-paragraph constructive understanding gives explanations, Students have fast knowledge and attention Executive in favor of females and realize syntactical in favor of males, and the results showed that executive attention and cognitive constructivist contribute to increasing cognitive speed and there is no differences between males and females to do so.
Keywords: الإرشاد التربوي -- السرعة المعرفية -- الانتباه التنفيذي -- المؤسسات التربوية -- طلبة المرحلة المتوسطة